DAMPAK PRESIDENTIAL THRESHOLD TERHADAP REGENT THRESHOLD - Harun Fadhli; Sarip Sarip; Nur Rahman (Jurnal De Jure Muhammadiyah Cirebon, 2021)
The election of the President and Vice President of Indonesia has experienced many dynamics from time to time. The beginning of independence, precisely on August 18, 1945, was carried out by the Preparatory Committee for Indonesian Independence (PPKI). the second replaces Sukarno. The minimum threshold (presidential threshold) became known in Indonesia in 2004, along with the issuance of Law no. 23/2003 concerning General Elections (Pemilu). The stipulation is that Political Parties (Parpol) must reach a minimum of 15% of the DPR seats and 20% of the national valid votes to be able to carry the president and vice president. Efforts to restore democracy to prevent the arbitrariness of the rulers through the presidential threshold have their own obstacles. The function of research is to seek the truth, truth is intended with regard to the nature, source, and scope of knowledge. Setting the Presidential Threshold in the presidential and vice presidential elections in Indonesia has had many impacts. So with the high Presidential Threshold, the public and political parties then submitted a judicial review to the Constitutional Court and in the Constitutional Court's decision Number 53/PUU-XV/2017 regarding the judicial review of Law No. 7/2017 article 222 which discusses the Presidential Threshold, the Constitutional Court refused. The refusal of judicial review of Article 222 of Law No. 7/2017 of the Constitutional Court resulted in setting the threshold for regional head elections still referring to Law No. 10/2016 on regional government. Keywords: threshold, political parties, local government, democracy.